Investigation on the transmission rate of carbapenemase-producing carbapenem-resistant Enterobacterales among exposed persons in a tertiary hospital using whole-genome sequencing. (June 2022) - Chang, E.; Chang, H.E.; Shin, I.S.; Oh, Y.R.; Kang, C.K.; Choe, P.G.; Park, W.B.; Choi, E.H.; Oh, M.D.; Park, K.U.; Kim, N.J.
Summary: Background: To reduce transmission of carbapenemase-producing carbapenem-resistant Enterobacterales (CP-CRE), screening is recommended for patients sharing rooms with CP-CRE-detected patients and healthcare workers caring for them. Aim: The aim of this study was to investigate the transmission rate of CP-CRE among exposed people in a tertiary hospital using whole-genome sequencing. Methods: This study was conducted in a 1751-bed tertiary teaching hospital from January 2017 to December 2019. Index patients were defined as those with positive results in CP-CRE tests during hospitalization. When an index patient was detected in a shared room, we performed CRE screening tests for patients whose stay overlapped with an index patient's stay for at least one day. Where a second case was found, healthcare worker contacts were also screened. CP-CRE were confirmed, and the carbapenemase type identified, by PCR. Whole-genome sequencing was used to compare isolates from index and exposed patients. Results: During the study period, 47 index patients were identified, and they had been in contact with 152 patients in shared rooms and 54 healthcare workers. None of the healthcare workers had CRE. Among the 152 exposed patients, four patients had the same type of carbapenemases as their CP-CRE index patients and all of them were KPC. Whole-genome sequencing revealed that three of these four pairs showed genotypic accordance between the index and the exposed. Conclusion: The CP-CRE transmission rate among the exposed patients was calculated as 2.0% (= 3/152).